Hydrogen radical-shuttle (HRS)-enabled photoredox synthesis of indanones via decarboxylative annulation - Bo Yang (Nature Portfolio, 2021)
Although hydrogen atom transfer is widely observed in synthetic organic chemistry, intramolecular hydrogen atom transfer between atoms separated by fewer than four bonds is kinetically slow. Here the authors show a method to form indanones, with hydrogen atoms shuttled across short distances by water.